ANALISIS KAIDAH FIKIH DALAM AKAD WADIAH DAN IJARAH SERTA IMPLEMENTASINYA DALAM PERBANKAN SYARIAH - Rofi'ah Alawiyah, Kiki; M. Fauzan , Januri (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
This study aims to examine the fiqh principles in the contracts of wadiah and ijarah and theirimplementation in Islamic banking. Wadiah itself is a contract between two parties where the first partyentrusts the authority and responsibility of property or goods to the second party without expecting anycompensation, while ijarah is a contract commonly used by financial institutions to facilitate leasing.The research method used is a qualitative approach with a literature study, where data is collectedthrough documentation such as classical books, contemporary works, scientific journals, and others.The research results show that there are several fiqh principles that align with the wadiah and ijarahcontracts, such as Adh-dhararu Yuzal, Al-Kharaj Bidhmman, al-ghurmu bilghumni, and others.Additionally, the implementation of wadiah is recognized in forms such as wadiah current accounts and wadiah savings accounts, while in ijarah, it is known through ijarah muntahiyya bittamlik and ijarahmutlaqah